Consistent or inconsistent? The effects of inducing cognitive dissonance vs. cognitive consonance on the intention to engage in pro-environmental behaviors - Bosone, Lucia; Chevrier, Marie; Zenasni, Franck (Frontiers in Psychology, 2022)
How do individuals rationalise the cognitive dissonance between their environmental awareness and the maintenance of environmentally unfriendly behaviors? The main goal is to explore the rationalisation strategies used by individuals in order to maintain their current behaviors. The secondary goal is to understand if it is possible to induce cognitive consonance, and how this influences intention to change. We present a study (N=222) with three experimental conditions: inconsistency, control, and consistency. The method to induce inconsistency and consistency was inspired by the paradigm of induced hypocrisy. Results demonstrated that induced inconsistency elicits two main barriers in participants: considering the change as unnecessary, and perceiving to lack knowledge about how to change. Induced consistency elicits tokenism, resulting in a licensing effect. However, behavioural intentions did not differ among experimental groups. Results are discussed considering methodological limitations and possible intervening variables.